2017
DOI: 10.18844/prosoc.v3i4.1511
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate governance on information asymmetry in Slovakia

Abstract: The consequences of poor management in companies are expressed fully and affect not only the companies themselves, but the entire world economy. Especially for multinationals we note one important factor which significantly influences their governance, namely the separation of ownership from management. The negative consequences of this separation force companies to greater transparency and responsible management through application of the principles of corporate governance. Applying the principles of corporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Wu et al, (2019) determine a negative relationship between independent directors and information asymmetry in USA firms. Musovaa et al, (2017) concluded that CG has a positive impact on reducing information asymmetry. Mali and Anis (2017) found that CG has a positive impact on information transparency in Tunisian institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al, (2019) determine a negative relationship between independent directors and information asymmetry in USA firms. Musovaa et al, (2017) concluded that CG has a positive impact on reducing information asymmetry. Mali and Anis (2017) found that CG has a positive impact on information transparency in Tunisian institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing literature focused on listed institutions to investigate the relationship of CG with information asymmetry however, not listed institutions are ignored largely. Few studies are, Wu et al (2019) on US institutions, Joudi et al (2019) on Iranian firms, and Tahir et al (2019) on Pakistani listed firms, the relationship between CG and disclosure quality of listed Pakistani institutions investigated by Nosheen and Sajjad (2018), Musovaa (2017) on listed firms of Bratislava Stock Exchange. Arslan and Alqatan (2020) and Arslan et al (2019) concluded that institutional determinants like legal, political, corruption, culture and values are very important to determine the practices of CG in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%